NILAI TAMBAH DAN PROSPEK PENGEMBANGAN AGROINDUSTRI KOPI HERBAL KAPULAGA DI DESA SUMBERPAKEM KECAMATAN SUMBERJAMBE - Beta Rianul Setiawati; Djoko Soejono (UPT Penerbitan Universitas Jember, 2018)
Herbal coffee cardamom is a coffee-based product processed from coffee and cardamom. Those agroindustry will sustain by pay attention to several things that affect production such as sustainability of production process. The purposes of this research was to know: (1) value added of herbal coffee cardamom product and (2) prospect development of herbal coffee cardamom agroindustry. The data analyzed by using value-added analysis and SWOT analysis. The result shows that; 1) Herbal coffee cardamom product has positive value added, and 2) Development prospect of herbal coffee cardamom agroindustry is about the position of cardamom herbal coffee agroindustry which is in the Gray Area (Weak-Potential Field) with a concentrated strategy through horizontal integration or stability.